Analysis of Teacher Needs for A Contextual Chemistry Module Based on Multiple Representation Integrated Islamic Values in Hydrocarbon Materials - Salma Salsabila; Nurfina Aznam (Indonesian Journal of Chemical Education, 2024)
This research aims to analyze the need for the development of a contextual chemistry module based on multiple representations integrated with Islamic values in hydrocarbon materials. This research method is qualitative descriptive research with data collection techniques in the form of structured interviews using interview guidelines for chemistry teachers at Madrasah 'Aliyah. The data analysis technique used is Miles-Huberman Interactive Analysis with stages of data collection, data display, data reduction, and drawing conclusions. The research findings reveal: 1) The curriculum implemented in schools is the independent curriculum. 2) Most students show a lack of interest in chemistry, particularly in hydrocarbon topics. 3) Students' religious character has declined. 4) The integration of Islamic values in learning is suboptimal and teachers possess limited knowledge of scientific developments. 5) No learning resources based on multiple representations and integrated with Islamic values are available. Based on the needs analysis conducted, a chemistry module with a contextual approach based on multiple representations integrated with Islamic values in hydrocarbon materials can be developed.